The relationship between students' perception of their Islamic practices and the perceived achievements of the IIUM mission - Adetunji, Busari Kazeem (Institute of Education, International Islamic University Malaysia, 2012)
The main purpose of the study was to investigate the students' perceptions of Islamic practices and how it influences in perceived mission achievement of International Islamic University Malaysia's (IIUM).The study employed quantitative research method specifically, a survey that used questionnaires as a method of the collection. A sample of 357 students was selected using stratified random sampling from the Institute of Education (INSTED) and the Kulliyyah of Islamic Revealed Knowledge and Human Sciences (IRKHS). Various statistical tools were employed such as descriptive statistics, factor analysis, t-test and correlation. The findings from the descriptive statistics showed that, majority of the respondents believed that they have strongly positive perceptions of their Islamic practice towards achieving the mission of IIUM. Further, factor analysis also indicated that six factors were extracted namely Management Mission, Articles of Faith, Pillars of Islam, Knowledge Culture, Islamic Principles and Islamic Culture/ Identity. The t-tests indicated that there was statistically significant difference between the local and international student's perception of their Islamic practice however, in term of gender, the male students perceived their Islamic practice slightly higher compared to their female counterparts, Although, the difference between male and female was not statistically significant. The findings from Pearson product moment showed a normal positive correlation between the student's perception of their Islamic practice (independent variables) and the IIUM perceived mission achievement (dependent variable).The implication from the study is that, the school management, educators, parents as well as the government need to collaborate, particularly in creating a favourable environment for the inculcation of Islamic practices. Based on the findings of the study, it is recommended that, institutionalization of programmes that will enhance clear understanding of Islam by students will help students in their willingness to internalize the Islamic practices. Future and in depth studies with regard to the Islamic practices in higher learning institutions are also recommended.